2017
DOI: 10.1161/jaha.116.004152
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Hypertrophy Regression During Antihypertensive Treatment in an Outpatient Clinic (the Campania Salute Network)

Abstract: BackgroundRegression of left ventricular (LV) hypertrophy (LVH) has been a goal in clinical trials. This study tests the external validity of results of clinical trials on LVH regression using a large registry from a tertiary care center, to identify phenotypes less likely to achieve regression of LVH.Methods and ResultsPatients from the Campania Salute Network, free of prevalent cardiovascular disease, but with echocardiographic LVH (defined as LV mass index [LVMi] >47 g/m2.7 in women and >50 g/m2.7 in men) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(58 citation statements)
references
References 48 publications
7
44
0
Order By: Relevance
“…This finding is fitting with other observations from the SHS and other epidemiological studies [3335], demonstrating disagreement between evolution of TOD and blood pressure.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is fitting with other observations from the SHS and other epidemiological studies [3335], demonstrating disagreement between evolution of TOD and blood pressure.…”
Section: Discussionsupporting
confidence: 91%
“…At 4.7-year follow-up of 8,479 persons, mean age 67 years old, with hypertension and electrocardiographic LVH diagnosed by the Cornell criteria, less severe electrocardiographic LVH was associated with a 19% reduction in heart failure hospitalization for every 817-mm·msec lower Cornell product (20). In an outpatient clinic, at 67-month follow-up of patients with hypertension and echocardiographic LVH, regression of LVH occurred in 23% of patients treated with antihypertensive drugs (21).…”
mentioning
confidence: 96%
“…Aggressive blood pressure control should be used to cause regression of LVH (21). A meta-analysis of 109 treatment studies including 2,357 patents with hypertension showed that angiotensinconverting enzyme inhibitors were the most effective antihypertensive drugs in reducing left ventricular mass (24).…”
mentioning
confidence: 99%
“…Moreover, BP-lowering drugs were shown to reduce LV mass [71] and improve LV diastolic function [72] thus reversing two major cardiac consequences of hypertension. Studies investigating sex-specific effects of anti-hypertensive treatment on LVH came to discrepant and inconclusive findings so far [73][74][75][76]. As such, more research is required to elucidate a potential sex-dependent response of the heart to antihypertensive therapy, but optimal BP control appears to be an effective strategy to diminish subclinical maladaptation of the heart in both men and women.…”
Section: Antihypertensive and De-stiffening Strategies For Heart Failmentioning
confidence: 99%